Religious Teacher Performance: Revitalization of Islamic Religious Education (IRE) Teachers As Innovators - Fitri, Agus Zaenul (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2018)
IRE teachers are the spearhead of success in learning religious education at schools. Curriculum changes will not have much impact on the quality of learning, if the quality of teachers is not improved. The strategy taken is to improve the performance and quality work of teachers, because the function of teachers are not only as an educator and facilitator, but also acts as an innovator in education. Innovators are not only means “changing